Layanan bimbingan kelompok dalam meningkatkan interaksi sosial siswa - Hafit Riansyah (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
This research aim to determine effectivity of group guidance service to increase student social interaction. This research is quantitative research with quasi experiment approach through nonequivalent control group design. Data were collected by questionnaire. Subjects in this research is 10 students. Data were analyzed with paired sample t test. The result of this research is group guidance service can increase student’s social interaction.